2020
DOI: 10.1007/s10930-020-09907-y
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Spectroscopy Detects Intermolecular β-Sheet Formation Above the High Temperature Tm for Two Monoclonal Antibodies

Abstract: The temperature-dependent secondary structure of two monoclonal IgG antibodies, anti-IGF1R and anti-TSLP, were examined by transmission mode Fourier Transform Infrared (FTIR) spectroscopy. Anti-IGF1R and anti-TSLP are IgG monoclonal antibodies (mAbs) directed against human Insulin-like Growth Factor 1 Receptor for anti-tumor activity and Thymic Stromal Lymphopoietin cytokine for anti-asthma activity, respectively. Differential scanning calorimetry (DSC) clearly indicates both antibodies in their base formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…The wavenumber of each secondary structure was determined through the second derivate method using the quadratic Savitzky-Golay smoothing (third-order polynomial with five points). The frequency of secondary structures was assigned as follows: intermolecular β-sheets 1611, 1618, 1625, and 1695 cm −1 [20][21][22]; intramolecular β-sheets 1674 cm −1 [23]; the bands between 1630 and 1640 cm −1 assigned to inter and/or intramolecular β-sheets [23,24], and called "β-sheets II"; β-turns 1668, 1682, and 1689 cm −1 [21,22]; α-helix 1645, 1651, and 1659 cm −1 [25][26][27]; and random coil 1645, 1651, and 1659 cm −1 [25,26]. Furthermore, the small bands' contributions due to side-chain (1594 and 1604 cm −1 ) and carboxylic groups adsorptions (1714, 1725, and 1731 cm −1 ) were also considered [25,28,29], but the quantification of secondary structures was carried out excluding those areas.…”
Section: Fourier-transform Infrared Spectroscopy Analysis (Ftir)mentioning
confidence: 99%
“…The wavenumber of each secondary structure was determined through the second derivate method using the quadratic Savitzky-Golay smoothing (third-order polynomial with five points). The frequency of secondary structures was assigned as follows: intermolecular β-sheets 1611, 1618, 1625, and 1695 cm −1 [20][21][22]; intramolecular β-sheets 1674 cm −1 [23]; the bands between 1630 and 1640 cm −1 assigned to inter and/or intramolecular β-sheets [23,24], and called "β-sheets II"; β-turns 1668, 1682, and 1689 cm −1 [21,22]; α-helix 1645, 1651, and 1659 cm −1 [25][26][27]; and random coil 1645, 1651, and 1659 cm −1 [25,26]. Furthermore, the small bands' contributions due to side-chain (1594 and 1604 cm −1 ) and carboxylic groups adsorptions (1714, 1725, and 1731 cm −1 ) were also considered [25,28,29], but the quantification of secondary structures was carried out excluding those areas.…”
Section: Fourier-transform Infrared Spectroscopy Analysis (Ftir)mentioning
confidence: 99%
“…12−16 In native globular proteins, β-sheet bands below 1630 cm −1 are rare. 17 Upon aggregation of monoclonal antibodies, Baird et al 18 identified a protein conformation characterized by β-sheet spectral features but absorbing at lower wavenumbers. The intramolecular β-sheet peak found at 1639 cm −1 in the native protein shifted to 1625 cm −1 .…”
mentioning
confidence: 99%
“…As recently reviewed, Fourier transform infrared (FTIR) spectroscopy is a powerful technique to determine the conformation of proteins in native and unfolded or aggregate states, for instance in amyloid structures. It is reported in the literature that FTIR spectroscopy has the potential to differentiate between different types of native secondary structures and even different types of aggregates. In native globular proteins, β-sheet bands below 1630 cm –1 are rare . Upon aggregation of monoclonal antibodies, Baird et al identified a protein conformation characterized by β-sheet spectral features but absorbing at lower wavenumbers. The intramolecular β-sheet peak found at 1639 cm –1 in the native protein shifted to 1625 cm –1 .…”
mentioning
confidence: 99%
“…When PEO was used to electrospin KS in an aqueous solution, a significant reduction in intramolecular β–sheet and intermolecular β–sheet was observed. Intramolecular β–sheets are formed within individual proteins, and intermolecular β–sheets are formed among separate proteins (causing protein aggregation) [ 23 ]. This result confirms that PEO interacts with polypeptide chains.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the second derivate method with a quadratic Savitzky-Golay smoothing (third-order polynomial with five points) was employed to determine the wavenumbers. The frequencies were assigned as follow: 1611, 1618, 1625, and 1695 cm −1 to intermolecular β–sheets [ 19 , 20 , 21 ]; 1674 cm −1 to intramolecular β–sheets [ 22 ]; the bands between 1630 and 1640 cm −1 can be assigned to inter and/or intramolecular β–sheets [ 22 , 23 ], and were called “β–sheets II” to express the presence of bands in this region; 1668, 1682 and 1689 cm −1 to β–turns [ 20 , 21 ]; 1645, 1651, 1659 cm −1 to α–helix [ 24 , 25 , 26 ]; 1645, 1651 and 1659 cm −1 to random coil [ 24 , 25 ]. Moreover, the small bands of side-chains (1594 and 1604 cm −1 ) and the bands of carboxylic groups (1714, 1725 and 1731 cm −1 ) were also taken into account [ 24 , 27 , 28 ]; however, those areas were excluded in the quantification of secondary structures.…”
Section: Methodsmentioning
confidence: 99%